THE IMPACT OF DIGITAL TRANSFORMATION ON ORGANIZATIONAL STRUCTURE AND DECISION-MAKING PROCESSES - Dabetić, Arsenije (Economic Outlook, 2024)
This paper explores the impact of digital transformation on organizational structure and decision-making processes. The aim of the research is to determine how technological innovations, such as cloud computing, artificial intelligence, and data analytics, are changing traditional management and organizational models. The main hypothesis is that digital transformation leads to the decentralization of decision-making and more agile organizational structures. The methods used in the research include case study analysis and a review of relevant literature. The results show that digitalization significantly affects management efficiency and employee productivity but also introduces new challenges, such as resistance to change and a lack of skills.
Keywords: digital transformation, organizational structure, decision-making, cloud computing, artificial intelligence.